Medicinal plants in the flora of Zhetysu Alatau, Zhetysu Region, Kazakhstan - Aknur Taldybay; Doctorkhan Aidarbayeva; Alfiya Kurmantayeva; Kuandyk Mussaev; Dinara Amanbekova; Botakoz Joltukova (Caspian Journal of Environmental Sciences)
The composition and ranking of medicinal plant species found in Zhetysu Alatau natural habitat are examined and reported in this study. The floristic analyses revealed that the studied region of Zhetysu Alatau has 201 species of medicinal plants, grouped into 125 genera and 37 families. Fabaceae has thirteen, Apiaceae eight, Rosaceae fourteen, Asteraceae twenty-one, and Lamiaceae twelve species. Additionally, information is provided on the stocks of significant medicinal plants in Zhetysu Alatau, including Jnula helenium L., Origanum vulgare L., Achillea millefolium L., and Hypericum perforatum L.